Histopathology and immunohistochemistry of large hepatocellular carcinoma with undetectable or low serum levels of alpha-fetoprotein - Wu, Qi-Ming (World J Gastroenterol, 1997)
AIM: To explore the pathomorphological characteristics of large hepatocellular carcinoma (LHCC) with low serum alpha-fetoprotein (AFP) level. METHODS: Specimens obtained from surgically resected LHCC with undetectable or low levels of serum AFP were fixed in formalin, embedded in paraffin, and prepared as serial sections. Routine hematoxylin and eosin as well as immunohistochemical stains (LSAB method) were used to test for expression of AFP, alpha-1-antitrypsin, epithelial membrane antigen, and vimentin. Some characteristics of the histopathological changes and immunohistochemical reactions of the cancerous tissues were observed under the light microscope. RESULTS: The majority of the cases (19/30) of LHCC with undetectable or low levels of serum AFP were of the clear-cell-type HCC, with 2 being positive for AFP expression at the periphery of the cytoplasm. CONCLUSION: The clear cell is the morphological manifestation of disturbance in glycogen and/or lipid metabolism of hepatoma cells. Such changes might be one of the factors hindering the synthesis of AFP and resulting in negative or low level serum AFP of the patient.